Economics of Inter-Cropping: A Case Study of Onion and Tomato at District Muzaffargarh, Punjab, Pakistan - Muhammad Nisar Khan,; Gulnaz Hameed,; Arshad Mahmood Malik,; Saima Asad, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The current research is being conducted in Muzaffargarh district of Punjab, Pakistan to investigate the profitability and land equivalent ratio of intercropping onion and tomato. An economic analysis of intercropping in the Muzaffargarh district can inform farmers about the profitability and sustainability of this practice, aiding their decision-making between intercropping and monocropping. The study utilized a simple random sampling technique to select 45 vegetable growers out of 60, from two major vegetable-growing villages; Hajiwah and Beli Janubi. Descriptive analysis, including frequency distribution, mean, and percentages, was used to analyze the data. The results of the study showed that intercropping had a significantly higher yield (17897 kg/acre) than sole cropping of onions (6075 kg/acre) and tomatoes (16050 kg/acre). Intercropping also had a higher benefit-cost ratio of 1.59, compared to onion sole cropping (1.37) and tomato sole cropping (1.48). The land equivalent ratio was 1.31, which indicated that intercropping was more efficient in terms of land use than sole cropping. The study also revealed that intercropping onions and tomatoes provided additional income to farmers and helped maximize land use. However, farmers encountered challenges such as high seed costs, diseases, low output prices, and high transportation costs. In conclusion, the study suggested that intercropping onion and tomato is a viable agronomic strategy in the Muzaffargarh district, as it improves land-use efficiency and maximizes returns. The study showed that intercropping complemented each other and contributed to increasing yield per unit area and improving nutritional properties.